Management of Fibroadenoma in a 12-Year-Old Dachshund Mix Dog - Rahmatullah, Aldin Akbar; Putri, Cindy Ercha Aulia; Ratnaningtyas, Nurrohmah; Pratama, Syifa Ramadhan; Karim, Nuurin Ajrin; Akintunde, Adeyinka Oye (Media Kedokteran Hewan, 2026)
Mammary tumors are a significant concern in canine veterinary medicine, with fibroadenoma being a rare benign subtype. This case report details the successful management of fibroadenoma in a 12-year-old, non-spayed, female Dachshund mix presenting with multiple abdominal masses (3–6 cm in diameter). Clinical examination showed stable vital signs (body temperature 38.5°C, pulse 110 bpm, respiratory rate 30 breaths/min). Diagnostic workup included ultrasonography, hematology, and histopathology, confirming fibroadenoma characterized by adenoma clusters within dense connective tissue. The term "adenomer" was clarified as a non-standard variant of adenoma, and consistent terminology was applied throughout. Treatment involved ovariohysterectomy and mastectomy, followed by post-operative administration of ceftriaxone, dexamethasone, amoxicillin, and metronidazole. The patient recovered without complications, underscoring the efficacy of early surgical intervention to prevent metastasis. This case highlights a comprehensive diagnostic and therapeutic approach for managing canine fibroadenoma.